2006
DOI: 10.1136/jcp.2005.028209
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic overexpression of ALCAM is prognostic of disease progression in breast cancer

Abstract: The data suggest that strong cytoplasmic ALCAM expression in primary breast cancer, as detected by immunohistochemistry, might be a new marker for a more aggressive breast cancer biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 34 publications
(29 reference statements)
6
76
2
Order By: Relevance
“…Over the last decade, alterations in ALCAM expression have been described in several other malignancies including bladder (6), colorectal (7), esophageal squamous cell (8), pancreatic (9), oral squamous cell (10) and ovarian cancer (11), neuroblastoma (12), prostate (13) and breast cancer (14,15). These data suggest that ALCAM expression is increased in some tumors and downregulated in others.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Over the last decade, alterations in ALCAM expression have been described in several other malignancies including bladder (6), colorectal (7), esophageal squamous cell (8), pancreatic (9), oral squamous cell (10) and ovarian cancer (11), neuroblastoma (12), prostate (13) and breast cancer (14,15). These data suggest that ALCAM expression is increased in some tumors and downregulated in others.…”
Section: Introductionmentioning
confidence: 67%
“…Some studies revealed an increased ALCAM expression to be associated with poor prognosis (15,17) or lymph node metastasis and local recurrence (18), while others found a decreased ALCAM expression to be linked to a poorer clinical course (14,19,20). One explanation for these conflicting data potentially lies in the relatively small number of breast cancer cases included in those studies, ranging from 56 to 347 (14,15,17,21). The aim of the present study was to clarify the prevalence and prognostic role of ALCAM expression in breast cancer using a pre-existing large-scale tissue microarray (TMA) including more than 2,000 breast cancer samples.…”
Section: Introductionmentioning
confidence: 73%
“…Second, multimerin-2 (Endoglyx-1) is a multisubunit glycoprotein of the vascular endothelium and may be associated with neoangiogenesis in melanoma metastases. 11 Third, CD166 (activated leukocyte-cell adhesion molecule, ALCAM) is a CD6 ligand, which is overexpressed in prostate, breast, and colon cancers 10 and controls invasive tumor growth. 23 Finally, lysosome-associated membrane glycoprotein-2 (LAMP-2, CD107b) is highly expressed in lung, protects the lysosomal membrane from autodigestion, and has been implicated in metastasis of pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered a prognostic marker in melanoma (van Kempen et al, 2000), prostate cancer (Kristiansen et al, 2005), breast cancer (King et al, 2004;Weichert et al, 2004;Burkhardt et al, 2006), colorectal cancer (Weichert et al, 2004), bladder cancer (Tomita et al, 2003), oesophageal squamous cell carcinoma (Verma et al, 2005) and ovarian cancer (Mezzanzanica et al, 2008). However, these data are quite inconsistent.…”
mentioning
confidence: 92%
“…However, these data are quite inconsistent. In some tumour types membranous expression is associated with worse prognosis (Weichert et al, 2004), whereas in other tumour types cytoplasmic localisation of ALCAM is an adverse prognostic parameter (Burkhardt et al, 2006). In addition, increased (Tomita et al, 2003;Weichert et al, 2004;Kristiansen et al, 2005;Verma et al, 2005;Burkhardt et al, 2006) as well as reduced (King et al, 2004;Mezzanzanica et al, 2008) expression of ALCAM has been correlated with poor prognosis, depending on the tumour type.…”
mentioning
confidence: 99%